2016
DOI: 10.1186/s12957-016-0904-7
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil/lymphocyte ratio has a prognostic value for patients with terminal cancer

Abstract: BackgroundDetermining prognosis in advanced cancer is of key importance. Various prognostic scores have been developed. However, they are often very complex. In this study, we evaluated the feasibility of neutrophil/lymphocyte ratio (NLR) as an index to estimate survival in terminal cancer patients.MethodsNLR was calculated retrospectively based on blood tests performed at 3 months, 2 months, 4 weeks, 3 weeks, 2 weeks, 1 week, and within 3 days before death in 160 cancer patients (82 men, 78 women; age range, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 17 publications
5
20
0
Order By: Relevance
“…In addition, in another cohort of 134 patients treated with later lines of chemotherapy, we show that NLR prognostic value was still independently associated with worse survival. These results are in line with the fact that the prognostic value of NLR has been demonstrated in a wide range of disease stages, from localized disease to patients receiving palliative care [ 33 ] or terminally ill [ 34 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In addition, in another cohort of 134 patients treated with later lines of chemotherapy, we show that NLR prognostic value was still independently associated with worse survival. These results are in line with the fact that the prognostic value of NLR has been demonstrated in a wide range of disease stages, from localized disease to patients receiving palliative care [ 33 ] or terminally ill [ 34 ].…”
Section: Discussionsupporting
confidence: 78%
“…Published data suggest high variability in the optimal NLR cut-off value, ranging between 1.9 and 9.21 [ 28 , 34 ]. In order to identify the optimal NLR cut-off value in our study, we performed extensive sensitivity analyses.…”
Section: Discussionmentioning
confidence: 99%
“…13 NLR has been shown to predict outcome in many diseases. It has been shown to have prognostic value to predict survival in terminal cancer 14 and cardiac mortality in stable coronary artery disease. 15 Lou et al 16 and Shiny et al 17 showed that NLR can be used as an indicator of systemic inflammation in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Up to date, only 4 studies have investigated the association between pre-treatment NLR and survival in cancer patients receiving palliative care and they all showed that the pre-treatment NLR was prognostically important 28 29 30 31 . However, unlike the existing 4 studies, whose study population was terminal cancer patients, we investigated the association in advanced cancer patients (including stage III and stage IV) as palliative care was integrated earlier in the course of advanced cancer in our country.…”
Section: Discussionmentioning
confidence: 99%